2021
DOI: 10.3389/fnagi.2021.649627
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Dopaminergic Neurons Changed Reversely With Those in the Midbrain via Gut Microbiota-Mediated Autophagy in a Chronic Parkinson’s Disease Mice Model

Abstract: The role of gut-brain axis in the pathogenesis of Parkinson’s disease (PD) have become a research hotspot, appropriate animal model to study gut-brain axis in PD is yet to be confirmed. Our study employed a classical PD mice model achieved by chronic MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) injection to study concurrent changes of dopaminergic neurons in the midbrain and the colon of mice. Our results showed such a PD model exhibited apparent locomotor deficits but not gastrointestinal dysfunction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…From the midbrain or striatum tissues, total proteins were extracted after being homogenized on ice in an ice-cold lysis buffer. Western-blot experiment methodology employed was the same as in our previously published studies [ 21 , 24 ]. Briefly, an equal number of proteins was separated using SDS-PAGE gels and transferred to PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…From the midbrain or striatum tissues, total proteins were extracted after being homogenized on ice in an ice-cold lysis buffer. Western-blot experiment methodology employed was the same as in our previously published studies [ 21 , 24 ]. Briefly, an equal number of proteins was separated using SDS-PAGE gels and transferred to PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…The gut microbiota changes found in colitis and rotenonetreated post-colitis mice in our study are similar to what has been observed in a study on another toxin-based PD mouse model, demonstrating an increasing trend in the RAs of Bacteroidetes and a decreased trend in the RAs of Firmicutes in PD mice [64][65][66] . In contrast, other studies show the opposite results 67 . We showed a lower abundance of Lactobacillus at the genus level in DSS alone and DSS+Rot group compared to the control group.…”
Section: Discussionmentioning
confidence: 87%
“…The vagus nerve, which supplies the brain with information from the entire GIT to the left colonic flexure, is generally accepted as the sensor of microbiota metabolites. EECs display a greater diversity and express a variety of proteins that act as signaling molecules on the various targets, both nearby and far away, with some of them demonstrating action in response to a variety of luminal stimuli. , The vagus nerve, the tenth cranial nerve, connects the digestive tract to the brain. It provides nerve endings to the digestive tract, allowing the CNS to control processes like gastric motility .…”
Section: Pathophysiology Associated With Parkinson’s Diseasementioning
confidence: 99%